Modelo de elementos finitos del hombro: comparación de los esfuerzos mecánicos de un hombro sano y un hombro con síndrome del manguito rotador (2015)
The aim of this study is to develop a numerical model of the shoulder, to determine the variation of mechanical stress in a healthy shoulder, and in another with rotator cuff syndrome, because in Colombia there are no studies to determine such efforts. A model was developed in three dimensions of the shoulder, from a set of computed tomography images. This model includes the humerus, scapula, glenohumeral ligament, rotator cuff tendons and articular cartilage.